Perancangan Sistem Penentuan Insentif Pegawai Menggunakan Metode Grey Relational Analysis - Hafiz, Aliy (Journal of Data Science and Information Systems, 2024)
Employee performance Incentive is an additional income given to employees as a form of appreciation for their contribution and performance in achieving company goals, this Incentive can be given based on the results of performance evaluations conducted by the company. The problem in determining employee incentives is the unclarity of performance evaluation criteria which can result in unfairness in determining the amount of incentives for each individual. In addition, if the incentive system cannot accurately consider individual contributions, it can hurt employees who work hard and are innovative but do not get the recognition they deserve, and potentially increase turnover rates in the company. Application of the Grey Relational Analysis (GRA) Method in employee performance appraisal involves several steps. First, determine the relevant performance appraisal criteria. Next, use the GRA method to calculate the level of relationship between each employee’s performance and predetermined criteria. By using GRA, it can determine the relative performance rating of each employee based on the level of conformity or relation to the criteria set. The final results of the employee ranking showed the results of the first rank with a GRG value of 3.4881 obtained by YSF Employees, the second rank with a GRG value of 3.1667 obtained by MD Employees, the third rank with a GRG value of 2.5238 obtained by PMB Employees. This result becomes a recommendation for companies in determining employee incentives using a decision support system model.